MULTI-SCENARIO SPATIAL MODELING OF PLTAL DISTRIBUTION IN INDONESIA TO SUPPORT CLEAN AND AFFORDABLE ENERGY - K. T. N. Ihsan; K. T. N. Ihsan; E. Sihotang; E. Sihotang; T. S. Anggraini; T. S. Anggraini (The International Archives of the Photogrammetry, Remote Sensing and Spatial Information Sciences, 2021)
Increasing consumption of non-renewable energy has become a topic of global problems today due to its limited availability with a high potential for environmental damage. Seeing these problems, it is necessary to develop renewable energy that is more environmentally friendly and has great potential in Indonesia. One of Indonesia’s potentials is an archipelago country with the second-largest coastline in the world with a coastline of 108,000 km. This causes Indonesia to have quite a large potential for ocean currents, namely around 1.5 m/s and reaching 2.5–3.4 m/s for the Nusa Tenggara region. The energy of ocean currents has the potential to be developed because of its relatively stable and predictable nature. Good planning by observing the potential resources and energy needs spatially is needed in the process of managing and utilizing energy in a maximum and sustainable manner. This study aims to analyze areas that have the potential to generate ocean current energy in Indonesia and utilize spatial and socioeconomic elements to determine the effective and efficient distribution of Ocean Current Power Plants (PLTAL), especially for coastal areas and small islands. This study will integrate multi-dynamic spatial data, such as ocean current data, electrification needs of each region, economic and transportation data, as well as a model of potential land availability based on remote sensing data. The result of this research is in the form of priority analysis of PLTAL development in Indonesia in terms of energy output, spatial aspects, and socioeconomic aspects. It is hoped that the results of this study can be used as considerations and solutions for policymakers in making decisions regarding the development of PLTAL in Indonesia, especially to meet the energy needs of coastal areas and small islands.